History and Foreign Policy - What is Old in Croatian Foreign Policy? - Jakovina, Tvrtko (Array, 2009)
History can be inspiration but at the same time very useful tool in foreign policy. Author is trying to show how paiful is the process of Croatian diplomatic practice when there is uneasines with certain historical periods.